TBIO-05. INTEGRATION OF GENOMIC DATA FROM THE ONCOKIDSSM NEXT GENERATION SEQUENCING PANEL AND CHROMOSOMAL MICROARRAY ANALYSIS FOR DIAGNOSIS AND PROGNOSIS OF PEDIATRIC CNS TUMORS. Issue 2 (22nd June 2018) - Kaneva, Kristiyana; Hiemenz, Matthew; Ji, Jianling; Robison, Nathan; Margol, Ashley; Dhall, Girish; Cotter, Jennifer; Hawes, Debra; Judkins, Alexander; Biegel, Jaclyn A
Abstract: OncoKids SM is a DNA and RNA-based Ampliseq panel designed at CHLA for clinical evaluation of pediatric hematologic malignancies and solid tumors. The DNA assay is designed to detect mutations in the full coding regions of 44 cancer loci; hotspot mutations in 82 genes; and amplification of 24 genes. The RNA content includes 70 driver genes and 1400 targeted gene fusions. Minimal input of 20ng DNA and RNA from frozen tissue or FFPE is required. To date we have prospectively evaluated 45 CNS tumor samples using OncoKids SM . Twenty-six of 45 tumors (57%) had at least one variant of strong clinical significance (Tier I). For 33 of the 45 cases (73%) we also performed copy number DNA-based chromosomal microarray (CMA). Results were consistent between the two platforms in 13 of 33 (39%) cases. CMA demonstrated increased clinical utility in 11 (55%) of the remaining cases, while OncoKids SM provided more clinically useful information in 9 of 20 (45%) cases. For low-grade gliomas, BRAF V600E mutations or KIAA1549-BRAF fusions were detected by both platforms, whereas for high- grade gliomas OncoKids SM demonstrated diagnostic and prognostic HIST1H3B, FGFR1, ACVR1, and TP53 Tier I mutations. OncoKids SM analysis also revealed potential germline mutations in cancer predisposition genes. In contrast, CMA had greater utility for embryonal tumors, e.g. medulloblastomas with chromosomal gains and losses consistent with Group 3/4 tumors that were non-informative by OncoKids SM . Our results demonstrate the clinical utility of CMA and OncoKids SM analyses for integrated reporting with pathology which have minimal sample requirements and rapid turnaround time.